PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING DENGAN MEDIA KONTEKSTUAL TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN KETERAMPILAN SOSIAL SISWA KELAS V PADA PEMBELAJARAN IPS - Hartini, Sri Hastuti Anwa; Alfansi, Ridho; Na’im, Mohamad (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to describe the impact of implementing the snowball throwing cooperative learning model with contextual media on the critical thinking skills and social skills of fifth-grade students. The study was conducted at SDN Sawaran Kulon 02 in Kecamatan Kedungjajang Kabupaten Lumajang. This research employs a quantitative approach using quasi-experimental research with a nonequivalent control group design. Two classes were involved class VA served as the experimental group, while class VB served as the control group. The research instruments used were social skills observation sheets and learning outcome tests. The analysis techniques included descriptive analysis, normality tests, paired sample t-tests, homogeneity tests, independent samples t-tests, N-Gain score tests, and independent t-tests for N-Gain scores. The results from the independent samples test yielded a significance value (2-tailed) of 0.000, which is less than 0.05, indicating a significant difference in the average learning outcomes between the experimental and control classes. It can be concluded that the implementation of the snowball throwing cooperative learning model with contextual media has a significant effect on students' critical thinking skills and social skills.